2012
DOI: 10.1039/c2nr31309j
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of a multifunctional carbon nanotube “cotton” yarn by the direct chemical vapor deposition spinning process

Abstract: A continuous cotton-like carbon nanotube fiber yarn, consisting of multiple threads of high purity double walled carbon nanotubes, was fabricated in a horizontal CVD gas flow reactor with water vapor densification by the direct chemical vapor deposition spinning process. The water vapor interaction leads to homogeneous shrinking of the CNT sock-like assembly in the gas flow. This allows well controlled continuous winding of the dense thread inside the reactor. The CNT yarn is quite thick (1-3 mm), has a highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Using this method, Li et al [129] firstly reported the continuous production of SWNTs. Soon thereafter, the continuous production of DWNTs was also reported by optimizing the temperature, precursor composition (both of the metal catalyst precursor and the sulfur/sulfur-containing molecule), as well as the aerosol generation conditions and reaction conditions [121][122][123].…”
Section: The Floating Catalyst Methodsmentioning
confidence: 99%
“…Using this method, Li et al [129] firstly reported the continuous production of SWNTs. Soon thereafter, the continuous production of DWNTs was also reported by optimizing the temperature, precursor composition (both of the metal catalyst precursor and the sulfur/sulfur-containing molecule), as well as the aerosol generation conditions and reaction conditions [121][122][123].…”
Section: The Floating Catalyst Methodsmentioning
confidence: 99%
“…According to previous reports, thread fibers normally present 6-8 % strain under stress before failure. [38,39] This strain will cause the SWCNT conductive network on the surface of thread fibers to generate a piezoresistive effect, which can be confirmed via micromorphological variation in the SWCNTs on them, as shown in Figure 2d. [40,41] Note that the SWCNTs used here were modified with a 2-4 nm coating of poly(3,4-ethylenedioxythiophene) polystyrene sulfonate (PEDOT/PSS).…”
Section: The Sensing Mechanism Of Swcnt-coated Threadsmentioning
confidence: 84%
“…The thermophoretic force is a result of temperature gradients and responsible for keeping CNTs from bonding on the reactor tube. Also (ii) Zhong et al [7,28] speculated that the van der Waals attraction leads to the sock formation. And (iii) Chaffee et al [29] mentioned that the nanotubes could form bundles due to electrostatic attraction.…”
Section: Sock Formation By the Convection Vortexmentioning
confidence: 98%
“…Motta et al [16] studied the effect of carrier gas and feedstock injection rate on the sock "spinnability" in a vertical furnace. Some mechanisms have been proposed for the sock formation, including thermophoresis or inertial migration [22], van der Waals attraction [7,28] and electrostatic attraction [29]. However, there is still significant ambiguity surrounding the understanding of how transport issues affecting the sock formation process.…”
Section: Introductionmentioning
confidence: 99%